2006
DOI: 10.1677/joe.1.06701
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen induces angiogenesis of the female rabbit bladder

Abstract: Postmenopausal bladder dysfunction has been speculated to involve decreased circulating estrogen levels. It is our hypothesis that estrogen induces bladder dysfunctions by modulating blood flow to the bladder, i.e. low estrogen reduces blood flow to the bladder, whereas high estrogen increases blood flow. Our previous studies have demonstrated that estrogen administration in female rabbits induces a 'functional hypertrophy' of the urinary bladder smooth muscle represented by increased smooth muscle mass, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 16 publications
(11 reference statements)
0
26
0
1
Order By: Relevance
“…2 vP and uP in ovx control animals are considerably lower than in E2 treated animals which confirms our previous observation. The increased bladder and urethral pressure are most likely due to increased muscular activity as a higher muscle mass of the detrusor and sphincter and higher blood supply was reported in ovx-E2 in comparison to untreated animals (Aikawa et al, 2003;Lin et al, 2006a;Lin et al, 2006b;Lin et al, 2006c). It appears that the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 6 phytoestrogens have similar, though weaker effects in the detrusor than in the sphincter apparatus.…”
Section: Discussionmentioning
confidence: 95%
“…2 vP and uP in ovx control animals are considerably lower than in E2 treated animals which confirms our previous observation. The increased bladder and urethral pressure are most likely due to increased muscular activity as a higher muscle mass of the detrusor and sphincter and higher blood supply was reported in ovx-E2 in comparison to untreated animals (Aikawa et al, 2003;Lin et al, 2006a;Lin et al, 2006b;Lin et al, 2006c). It appears that the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 6 phytoestrogens have similar, though weaker effects in the detrusor than in the sphincter apparatus.…”
Section: Discussionmentioning
confidence: 95%
“…Also, previous studies suggested that Ovx can cause a decreased of blood fl ow around the bladder neck and urethra, mucosal and smooth muscle atrophy, increased collagen synthesis and distribution, and decreased contractility. Estrogen replacement reduced the effects of Ovx and resulted in smooth muscle hypertrophy and enhanced contractility (27). Also it has been reported that estrogen mediates angiogenesis accounting for the increased vascular density and increased blood fl ow.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is essential for the mainenance of physiological function of the female urogenital tract. Previous studies have shown that bladder blood flow is regulated, in part, by estrogen [1]. In previous reports, ovariectomy resulted in decreased blood flow and hypoxia to the bladder mucosa and a mildly decreased blood flow to the smooth muscle as early as post-ovariectomy day 1.…”
Section: Introductionmentioning
confidence: 91%